Comparison of capillary blood glucose level at 1 h after induction of general anesthesia in children receiving intraoperatively either Ringer’s lactate with glucose 1% or Ringer’s lactate alone - Santra, Sayan; Mandal, Sangita; Chakraborty, Jayanta; Mandal, Mohanchandra (Asian Journal of Medical Sciences, 2022)
Background: Perioperative fluid therapy in children is quite challenging job for anesthesiologists. Variable glycemic control has been reported in the literature regarding the use of balanced electrolyte solution with or without 1–2% glucose supplementation. Aims and Objectives: Hence, this study was planned to determine the capillary blood glucose level (CBG) in the intraoperative period at 1 h after induction of general anesthesia in children (1–6 years of age) receiving either Ringer’s lactate (RL) with glucose 1% or RL alone. Materials and Methods: A total of 60 patients of either gender, aged 1–6 years, of American Society of Anesthesiologists Physical Status Classes 1 and 2 were included for this interventional study. All children received protocolized general anesthesia with strict adherence to standard fasting guidelines. The children received either RL alone (Group A, n=30) or RL plus 1% glucose solution (Group B, n=30) as intraoperative fluid. The pre-operative CBG was recorded. Intraoperative fluid was given at 10 mL/kg/hr. The CBG was checked again at 30 min and 1 h after induction of anesthesia. The glycemic status at 1 h in the intraoperative period was compared (primary outcome) between the two groups. Results: The hemodynamics and intraoperative consumption of fluid were comparable between the groups. The mean CBG values at 30 min and at 1st h were considerably higher in groups receiving RL with 1% glucose compared with those receiving RL alone. However, these differences were not clinically significant. No adverse event was observed. Conclusion: RL alone or RL plus glucose 1% can be used as intraoperative fluid in children (1–6 years of age). None developed clinically significant hypoglycemia or hyperglycemia. However, the optimal amount of glucose which can be safely used in the perioperative period needs to be determined with a larger trial.